Efektivitas Revitalisasi Ruang Publik Pasar Sindang Sari Kecamatan Toili Barat Kabupaten Banggai - Adiliya, Putri; Natsir, Nawawi; Aqib (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
Market revitalization is a government initiative aimed at improving trading facilities and strengthening the role of traditional markets as centers of community economic activity. This study examines the effectiveness of public space revitalization at Sindang Sari Market, West Toili District, Banggai Regency. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Informants included the Head of the Market Management Unit, officials from the Department of Industry and Trade of Banggai Regency, market managers, and traders. Data analysis used an interactive analysis model that includes data collection, condensation, data presentation, and drawing conclusions. This study uses the theory of organizational effectiveness that includes goal achievement, integration, and adaptation. The findings indicate that revitalization has improved the market’s physical condition through the construction of stalls, trading spaces, drainage systems, sanitation facilities, and other supporting infrastructure. However, the program has not achieved optimal effectiveness due to the limited use of stalls, insufficient socialization efforts, low trader adaptation to the new facilities, and inadequate maintenance of several facilities. Therefore, improved market management, facility maintenance, and stronger communication between the government and traders are needed to maximize the outcomes of the revitalization program.